1997
DOI: 10.1080/07391102.1997.10508199
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Interactions of the Oligodeoxyribonucleotides on the Complementary Template. The Influence of Chemical Groups and Mismatched Nucleotides at the 5′- and 3′-ends of Oligonucleotides on the Parameters of Cooperativity

Abstract: Parameters of cooperative interactions of two or three oligodeoxyribonucleotides or their derivatives bound with the adjacent sites of the complementary template were measured using method of "complementary addressed modification titration" (CAMT). Complementary template (target) were modified with the reactive oligonucleotide derivatives (reagents) bearing covalently attached alkylating 4-[N-(2-chloroethyl)-N-methylamino]benzylamino- group (C1RCH2NH)- at 5'-terminal phosphate. The targets had only one binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The effect of base stacking on the cooperativity of DNA duplex formation was investigated before via chemical ligation of a reporter oligonucleotide to its template in the presence and absence of a third oligonucleotide bound adjacently to the template. [2][3][4] It was shown that two pyrimidine bases at the junction site lead to no increase in the binding constant of the reporter oligonucleotide, while a 28-fold enhancement was observed when two guanines are next to each other, indicating a considerable positive cooperative effect for strand association mediated by purine stacking. 4 A similar situation is encountered in DNA triplex formation of two adjacent pyrimidine strands on a DNA duplex template.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of base stacking on the cooperativity of DNA duplex formation was investigated before via chemical ligation of a reporter oligonucleotide to its template in the presence and absence of a third oligonucleotide bound adjacently to the template. [2][3][4] It was shown that two pyrimidine bases at the junction site lead to no increase in the binding constant of the reporter oligonucleotide, while a 28-fold enhancement was observed when two guanines are next to each other, indicating a considerable positive cooperative effect for strand association mediated by purine stacking. 4 A similar situation is encountered in DNA triplex formation of two adjacent pyrimidine strands on a DNA duplex template.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative understanding of DNA sequence-dependent thermodynamic stability and solution hybridisation behaviour would have direct practical applications in the design of multiplex reactions (12). In this regard, co-operative parameter interactions at the nick position have previously been calculated using a complementary addressed modification titration (CAMT) method (13)(14)(15). Free energy values of coaxial stacking for a range of possible interaction types at a nick position have also been determined for two-strand systems where a short strand contiguously stacks to a hairpin oligonucleotide (16,19).…”
Section: Introductionmentioning
confidence: 99%